Pengaruh Pendapatan Asli Daerah Terhadap Pertumbuhan Ekonomi di Kabupaten Paser Tahun 2010-2020 - Ihsan, Muhammad Khairani; Nuryadin, Muhammad Rusmin (PPJP Universitas Lambung Mangkurat, 2023)
This study aimed to determine the size of the ratio and components of regional original income and determine the economic growth in Paser Regency from 2010 to 2020. The data collection techniques in this study were publication and documentation. The analysis technique uses the method of calculating financial performance and ordinary least squares (OLS). The results of this study indicate that the calculation of the two ratios for ten years has fluctuated. The average of this Efficiency Ratio is 76.67 Percent. At the same time, the average effectiveness ratio is 117.28 percent. The regression analysis results show that local taxes have a positive and significant effect on economic growth. In contrast, regional levies negatively and significantly impact economic growth. The results of separated regional wealth management and other legitimate local revenue have a negative and non-significant effect on the development of the Economy.